ショウワキチ デ サイカイ サレタ NOAA エイセイ ジュシン ノ ガイヨウ ト ショキテキ セイカ - 平沢, 尚彦; ヒラサワ, ナオヒコ; 改井, 洋樹; カイ, ヒロキ; 山内, 恭; ヤマノウチ, タカシ; Hirasawa, Naohiko; Kai, Hiroki; Yamanouchi, Takashi (2002)
P(論文) NOAA衛星受信が1997年3月に昭和基地で再開された。この設備更新により, かつては1日に1パス程度の受信が運用の限界であったものが, DMSP衛星, NOAA衛星を合わせて20パス程度の受信が可能となった。昭和基地では受信データを画像化し基地内LANを介してのweb公開を行い, 観測隊の活動計画立案の有益な資料として利用している。受信データは年に1度持ち帰られ, 国立極地研究所情報科学センターのテープライブラリ装置に格納され, 共同研究に供されている。現在行っている受信は12号, 及び14号であり, おおよそ11UTから03UTの間に対応している。1日に複数パスが揃う気水圏関連の衛星データセットは昭和基地ではこれまでになく, 東南極域の低気圧の活動度や海氷分布の変化をこれまでより詳細に理解出来ることに加え, 南極氷床の涵養・消耗をつかさどる水収支に密接に関連する夏季の惑星境界層の日変化についての議論が可能となる。また, 内陸の雲域には従来の検出方法では検出できない場合があることが分かった。ドームふじ観測拠点での大気観測データを合わせて利用することにより, 南極域の雲の知見を広げ, 雲検出方法が改良されることが期待される。 NOAA satellite data acquisition was resumed at Syowa Station in March 1997. As a result of replacement of the facility, the capacity of operation for satellite receiving and data processing was improved to permit receiving of all NOAA and DMSP transmission (except for their simultaneous coming), about twenty passes a day. It was limited to one pass a day in a past. The received data are imaged immediately at the station, and set on the web-site which is available in the LAN of only Syowa Station. These data are also positioned as effective information to decide schedule of field works. Data are being archived in the tape library in the Information Science Center of National Institute of Polar Research. At present data from NOAA-12 and NOAA-14 are received. The time zone between 11 UT and 03 UT is covered. The NOAA data acquired at the highest frequency in our past data set at Syowa Station permit us to understand cyclonic activity and sea ice variation in the east Antarctic region better than in the past. Also, we expect to discuss the daily variation of the planetary boundary layer over Antarctica, which is closely associated with the water budget of the ice sheet. In some cases the conventional cloud detection method cannot be used to determine the cloud area over the inland of Antarctica in winter. It is possible to develop a cloud detection method through better understanding of cloud features in the inland of Antarctica with the NOAA data and atmospheric data sets obtained at Dome Fuji ...